PENGARUH MODEL EXAMPLE NON EXAMPLE TERHADAP HASIL BELAJAR MATERI POKOK UANG DI SMA NEGERI 5 PADANGSIDIMPUAN - Mhd. Nau Ritonga; Sri Hartini; Nurul Mawaddah (Institut Pendidikan Tapanuli Selatan, 2021)
This study aims to find out: 1) how the description of the use of the non-example model in class X SMA Negeri 5 Padangsidimpuan, 2) how the description of student learning outcomes on the subject matter of money before and after using the non-example model in class X SMA Negeri 5 Padangsidimpuan, c ) is there a significant effect between the use of the example non example model on student learning outcomes on the subject matter of money in class X SMA Negeri 5 Padangsidimpuan. The time of the study was carried out for 4 months starting from February to May 2021. The research method used is descriptive quantitative research method. The population in this study were 30 students. The technique used is the total sample. Data collection techniques obtained by questionnaires and tests. Technical data analysis uses descriptive data and inferential statistical analysis. Based on the calculations obtained from the results of data processing using SPPS Software Version 22, the results of the model variable example non example (variable X) obtained a t-test index of 2.229 while t-table was 1.697 with a significant value = 0.034. Then it can be seen that it is significantly smaller than a (0.034 < 0.05). So it can be concluded that the hypothesis Ha is accepted and Ho is rejected. This means that there is a significant influence between the non-example model of learning outcomes for the subject of money in class X SMA Negeri 5 Padangsidimpuan,